Oligomerization of optically active N-(4-hydroxyphenyl)mandelamide in the presence of β-cyclodextrin and the minor role of chirality - Ritter, Helmut; Stöhr, Antonia; Favresse, Philippe (Beilstein Journal of Organic Chemistry, 2014)
The oxidative oligomerization of a chiral mandelamide derivative (N-(4-hydroxyphenyl)mandelamide, 1) was performed in the presence of horseradish peroxidase, laccase and N,N'-bis(salicylidene)ethylenediamine-iron(II) to obtain chiral oligophenols 2. The low enantioselectivity of the enzymatic catalyzed asymmetric enantiomer-differentiating oligomerizations was investigated. In addition, the poor influence of cyclodextrin on the enantioselectivity of enzymatic catalyzed asymmetric enantiomer-differentiating oligomerizations was studied.
Keywords: cyclodextrin; enantioselectivity; enzyme; oxidative coupling; phenol oligomer